Cannabinoids reduce hyperalgesia and inflammation via interaction with peripheral CB1 receptors - Richardson, Jennelle Durnett; Kilo, Sonja; Hargreaves, Kenneth M (Pain (Amsterdam), 1998)
Central antinociceptive effects of cannabinoids have been well documented. However, relatively little is known about the peripheral effects of the cannabinoids on inflammation. In the present study, we evaluated the effects of peripherally administered cannabinoids on three indices of inflammation: carrageenan-induced thermal hyperalgesia, carrageenan-induced edema, and capsaicin-induced plasma extravasation. In addition, we determined the effect of cannabinoids on capsaicin-evoked neuropeptide release from isolated rat hindpaw skin. Our results indicate that cannabinoids produce antihyperalgesia via interaction with a peripheral CB1 receptor. Peripheral, but not systemic, administration of 0.01 ng anandamide inhibited the induction of hyperalgesia. Peripheral administration of anandamide also attenuated hyperalgesia after its development via interaction with the CB1 cannabinoid receptor subtype as indicated by its reversal with the CB1 receptor antagonist SR 141716A. Additionally, peripheral, but not systemic, administration of 0.01 ng anandamide inhibited edema. Peripherally administered cannabinoids also interacted with CB1 receptors to inhibit capsaicin-evoked plasma extravasation into the hindpaw. One potential mechanism for the anti-inflammatory actions of the cannabinoids is the inhibition of neurosecretion from the peripheral terminals of nociceptive primary afferent fibers. This hypothesis is supported by the finding that anandamide inhibited capsaicin-evoked release of calcitonin gene-related peptide from isolated hindpaw skin. Collectively, these results indicate that cannabinoids reduce inflammation via interaction with a peripheral CB1 receptor. A potential mechanism for this effect is the inhibition of neurosecretion from capsaicin-sensitive primary afferent fibers.